Service Effectiveness and Use of Website Media in Bantul Regency Government - Beltahmamero Simamora (PERSPEKTIF, 2023)
Currently, the government is faced with high demands to provide information disclosure to the public. In addition, the community's need for public services is also increasing. This condition is a fact for city or regency governments in Indonesia, including Bantul Regency. Through this research, researchers intend to analyze the bantulkab.go.id website media from the perspective of service effectiveness and usage. This research uses descriptive qualitative methods with data obtained from primary and secondary sources. The result of the research is that the effectiveness of services between the government and the community has not run optimally, especially due to communication. This is evidenced by the uncertainty of the District Government in responding to public complaints that enter through the website. Furthermore, from the aspect of website usage, over time the number of users has decreased. The implication of this research is that the Bantul Regency Government needs to increase responsiveness and responsibility for reports from the community. In addition, the government needs to improve the quality of the website and the features/facilities on the website.